1992
DOI: 10.1210/endo.130.4.1547734
|View full text |Cite
|
Sign up to set email alerts
|

Androgen and progesterone receptors in shark (Squalus) testis: characteristics and stage-related distribution.

Abstract: Although testosterone (T) is essential for the normal completion of spermatogenesis, the exact T-sensitive control points are still unknown. Using staged tissues (premeiotic, PrM; meiotic, M; and postmeiotic, PoM) from zonal testes of the spiny dogfish Squalus acanthias, and standard [3H] steroid binding analysis, we characterized a T-binding component with physiochemical characteristics resembling classical androgen receptors (AR). [3H]T binding was of high affinity (dissociation constant = 4.4 x 10(-9) M), l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 27 publications
3
20
0
Order By: Relevance
“…In our study, the optimum 22a-hydroxycholesterol concentration required to elicit the maximum rates of steroido¬ genesis (100-200 pmol l-1 depending on the steroid and on the nature of the lobule) was comparable to that required for rat Leydig cells (100 pmol 1" \ Risbridger et al, 1986 (Hall et al, 1969;Cooke et al, 1972) and that rat Sertoli cells cannot convert pregnenolone to progesterone (Wiebe et al, 1988 Kime (1978) and Cuevas and Callard (1992) (Sourdaine et al, 1990 (Dobson and Dodd, 1977), as observed in Torpedo marmorata and T. ocellata by Fasano et al (1989). This highlights the importance of the contribution of testicular paracrine mechanisms and, in particular, the effects of germ cells for the control of steroid production.…”
Section: Introductionsupporting
confidence: 47%
“…In our study, the optimum 22a-hydroxycholesterol concentration required to elicit the maximum rates of steroido¬ genesis (100-200 pmol l-1 depending on the steroid and on the nature of the lobule) was comparable to that required for rat Leydig cells (100 pmol 1" \ Risbridger et al, 1986 (Hall et al, 1969;Cooke et al, 1972) and that rat Sertoli cells cannot convert pregnenolone to progesterone (Wiebe et al, 1988 Kime (1978) and Cuevas and Callard (1992) (Sourdaine et al, 1990 (Dobson and Dodd, 1977), as observed in Torpedo marmorata and T. ocellata by Fasano et al (1989). This highlights the importance of the contribution of testicular paracrine mechanisms and, in particular, the effects of germ cells for the control of steroid production.…”
Section: Introductionsupporting
confidence: 47%
“…Although our findings provide no insight regarding the mechanism of the Cd-stimulated increase in the apoptosis of early-stage PrM cysts, the observed presence of a second nuclear-associated component of 109 Cd which is detected in greater amounts in PrM cysts than in PoM cysts (Betka and Callard, 1999), certainly implicates Cd in nuclear-associated activities in the intact spermatogonium/Sertoli cell units. Of interest, classic androgen and estrogen receptors are known to be concentrated in the PrM region of Squalus testis (Callard et al, 1985;Cuevas and Callard, 1992). In this regard, the potential for dysregulation of steroid-mediated activities is significant, given that Cd mimics the in vivo effects of estrogen in the uterus and mammary gland (Johnson et al, 2003), directly inhibits and/or activates androgen and estrogen receptors in mammalian (Martin et al, 2002;Takiguchi and Yoshihara, 2006) and fish (Guevel et al, 2000;Vetillard and Bailhache, 2005) steroidresponsive cells and tissues.…”
Section: Discussionmentioning
confidence: 99%
“…McClusky, unpublished observations). By extension and given that (1) mature spermatid cysts, which are absent in April -May, are major sites for the synthesis of androgen-binding protein and for the secretion of testosterone and its precursors (Simpson & Wardle 1967, Mak & Callard 1989, Sourdaine et al 1990, Cuevas & Callard 1992a, (2) classical nuclear oestrogen and androgen receptors are concentrated in the PrM region of the shark testis (Callard et al 1985, Cuevas & Callard 1992b, (3) the vascular pathway in Squalus is countercurrent to the spermatogenic progression, i.e. PoM cysts to GZ cysts (Cuevas et al 1992) and (4) hypophysectomy of male dogfish (Scyliorhinus) leads only to a small decrease in circulating androgen (Dobson & Dodd 1977a), overall reconciliation of all these observations in dogfish sharks suggests that the developmental advance of mature spermatogonial cysts in sharks is dependent not only on de novo testosterone and/or oestrogen synthesis in PrM cysts, but also on those synthesized in mature-spermatid cyst stages, when they are present in the spermatogenic progression.…”
Section: Discussionmentioning
confidence: 99%